2023
DOI: 10.3390/jcm12134508
|View full text |Cite
|
Sign up to set email alerts
|

Which of 51 Plate Designs Can Most Stably Fixate the Fragments in a Fracture of the Mandibular Condyle Base?

Abstract: In the surgical treatment of the most common fracture of the mandible, which is a fracture of the condylar base, a great choice of different plate shapes is observed. The aim of this study was to determine which shape gives the greatest fixation stiffness. To ensure homogeneity in comparison, tests were performed on polyurethane models divided at the level of the condylar base fracture and each were fixed with 51 plates. The plates were cut from a 1 mm thick grade 23 titanium sheet. The models were then loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Evaluation of the influence of oval holes showed that they have an adverse effect on the rigidity of the fixation, which can be seen in the delta plate (plate 2 vs. plate 37) or XCP (plate 19 vs. plate 40). The best plates are those fixed with seven, eight, or nine screws [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of the influence of oval holes showed that they have an adverse effect on the rigidity of the fixation, which can be seen in the delta plate (plate 2 vs. plate 37) or XCP (plate 19 vs. plate 40). The best plates are those fixed with seven, eight, or nine screws [21].…”
Section: Discussionmentioning
confidence: 99%
“…These polyurethane mandibular models were standardized and featured a uniform internal structure, closely mimicking the properties of human spongy bone. Polyurethane mandibles from Sawbones (Vashon, WA, USA; density 0.16 g/cc, compression modulus 58 Mpa) served as the testing models [9,[17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These models are made of a material that mimics the properties of spongy bone in humans. Specifically, for strength assessments, we employed polyurethane mandibles (Sawbones, Vashon, WA, USA: density 0.16 g/cc, compression modulus 58 MPa) [13][14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…The PDF (Plate Desing Factor) [19] and MEF (Mechanical Excellence Factor) [17] already recommended by the authors were determined for each plate (Table 1). The PDF (Plate Desing Factor) [19] and MEF (Mechanical Excellence Factor) [17] already recommended by the authors were determined for each plate (Table 1).…”
Section: Methodsmentioning
confidence: 99%